Incentives Matter: Reflections on the Role of Incentives in Scientific Productivity - Raul V. Fabella (Philippine Institute for Development Studies (PIDS), 2013)
Depicting the Philippines as a prescientific society, this paper discusses how the environment plays a significant role in shaping the culture of research and scientific productivity. Such conducive environment includes having an adequate think space, a supportive and engaging critical mass, and most importantly, an efficient incentives system. The paper cites several examples of research institutions in the Philippines which highlighted the importance of collaborative efforts, research networks, strong leadership, and generous rewards in attaining success in their endeavor. It also mentions detriments to productivity such as implicit publication costs, the politics of fairness of equality, and the bias for quantity over quality.
Keywords: I23; 330; Philippines; research culture; research incentives; research institutions